Maturacao para colheita de sementes em (Stylosanthes macrocephala M.B., Ferr. et Sousa Costa) - Carmona, R; Ferguson, John E.; Souza Maia, M. de (1986)
This experiment was carried out to determine the yield and seed quality from seed harvested on the plants and seed shattering in S. macrocephala in Carimágua, Colômbia, in 1983. The experimental design was a completely randomized block with 4 replications. The seed samples were colleted between 57 and 92 days after anthesis. The shattering seeds were sampled in plastic trays. The higher yield of pure viable seeds on the plants was obtained from 65 to 80 days after anthesis, which it is the suitable time for harvesting. On the second week of this period, the yield of pure seeds was less, however with high viability. The seed shattering increased as harvest was delayed. The parameters, such as: seed moisture (40-50%) bottom color, pod color and seed shattering were good indicators of harvesting time.